Neovascularization after ischemic conditioning of the stomach and the influence of follow-up neoadjuvant chemotherapy thereon - Prudius, Vadim; Procházka, Vladimír; Pavlovský, Zdeněk; Peštál, Adam; Vlček, Petr; Čapov, Ivan; Veverková, Lenka; Reška, Michal (Wideochirurgia i inne techniki maloinwazyjne, 2018)
INTRODUCTION: Esophagectomy and reconstruction remain the optimal treatment for patients with resectable esophageal cancer. Neovascularization after ischemic conditioning of the stomach before esophagectomy is a laparoscopic procedure which may potentially reduce gastric conduit ischemia. AIM: To investigate the influence of ischemic conditioning on neovascularization along the greater curvature of the stomach and to explore the effect of neoadjuvant chemotherapy on neovascularization after ischemic conditioning. MATERIAL AND METHODS: Staging laparoscopy was performed before the main resection procedure; during this procedure ischemic conditioning was performed. Samples taken from the human stomach were divided into 3 groups: group A - patients after ischemic conditioning with a delay of 30-45 days after left gastric artery (LGA) ligation (n = 4); group B - patients who were undergoing neoadjuvant chemotherapy with a delay of 90-140 days after left gastric artery ligation (n = 4); and control group C - patients without ischemic conditioning (n = 7). RESULTS: After ischemic conditioning with a delay of 30-45 days, the count of neovessels along the greater curvature of the stomach increased from 5.4 ±0.7 in the control group to 17.5 ±0.9 in a low-power field of view (LPF) in group A and increased still further on average to 19.8 ±10.4 in group B. CONCLUSIONS: Left gastric artery ligation only is a sufficient procedure for ischemic conditioning of the stomach. Neovascularization along the greater curvature is a continuous process that depends on delay time. Neoadjuvant therapy has no influence on the effect of neovascularization.
Keywords: gastric conduit; esophageal cancer; ischemic conditioning; esophageal surgery; neovascularization